An alternative method to access diverse N, N′-diquaternised-3, 3′-biquinoxalinium "biquinoxen" dications. (15th March 2017) - Leblanc, Nicolas; Sproules, Stephen; Powell, Annie K.
Abstract : Biquinoxens synthesis via oxidative radical homocoupling of N -alkylquinoxalinium – an alternative method. Abstract : An alternative synthetic route for the design of N, N ′-diquaternised-3, 3′-biquinoxalinium "biquinoxen" dications is reported, involving oxidative radical coupling of dithionite reduced quinoxaline quaternary salts. Although the reaction is not regioselective, leading to relatively modest yields (up to 32%), the advantages of this new synthetic protocol lie in a simple potentially gram scale synthesis using inexpensive easily accessible reagents with no metal catalysts and no purification steps. Thus whereas the method reported previously to access the N, N ′-dimethyl-3, 3′-biquinoxalinium, "methylbiquinoxen" precursor gave higher yield than the new method reported here, this new method avoids the limitation of using scarce oxonium reagents. Overall, the new protocol is a robust synthetic strategy which offers new design possibilities.